AB0412 Exploratory Results from The Bliss and Illuminate Trials Support The Design of The CHABLIS-SC1 Trial, A Randomized, Double-Blind, Placebo-Controlled Phase 3 Study To Evaluate The Efficacy and Safety of Blisibimod Administration in Subjects with Systemic Lupus Erythematosus. (15th July 2016) - Merrill, J.T.; Strand, V.; Hislop, C.; Gangal, M.; Martin, R.S.; Kalunian, K.C.
Abstract : Background: Targeted, biologic inhibitors of B-cell Activating Factor (BAFF) have been evaluated in 4 large Phase 3 clinical trials in nearly 4000 patients with Systemic Lupus Erythematosus (SLE). Data from these studies identify that greatest treatment effect is discernable using more stringent endpoints in patients who enter with higher disease activity scores, taking more corticosteroids, and/or have anti-double-stranded DNA (dsDNA) and low complement C3 or C4 1, 2, 3 . Objectives: The CHABLIS-SC1 study (NCT01395745 ) has completed enrollment and will be the first trial to prospectively evaluate the impact of treatment on the above "responder populations" using the BAFF inhibitor, blisibimod. Methods: CHABLIS-SC1 enrolled subjects positive for anti-nuclear and/or anti-dsDNA antibodies with SELENA-SLEDAI≥10 despite corticosteroid therapy. Subjects were randomized to have blisibimod or placebo added to their background medications. Efficacy will be evaluated using the SLE Responder Index-6 (SRI-6) at Week 52, defined as: ≥6 point reduction in SELENA-SLEDAI; no new BILAG A or 2 new BILAG B organ domain scores; and no worsening in Physician's Global Assessment. Results: Table 1 identifies that the baseline characteristics of the 442 subjects enrolled into the CHABLIS-SC1 study more frequently meet all descriptions of "responder populations" identified previously 2–7 . In previous studies, the SRI-6 was associated with lower placebo responder rates and greater benefit of BAFF inhibitors over placebo. Conclusions: BAFF inhibitors are known to be at least modestly effective in SLE and impact B Cell-driven immunopathology such as autoantibodies. The CHABLIS-SC1 study design will determine whether enrichment for the hypothesized "responder population, " patients with more severe, immunologically active SLE, will robustly discriminate treatment impact of blisibimod when background therapy is maintained. References: van Vollenhoven RF et al. Ann Rheum Dis. 2012;71:1343. Isenberg DA, et al. Ann Rheum Dis. 2015 Sep. Merrill JT et al. Ann Rheum Dis. 2015 Aug. Dooley MA et al Lupus, 2013;22(1):63, Manzi et al Ann Rheum Dis. 2012;71(11):1833, Merrill et al 2015 (EULAR abstract); Benlysta FDA Drug Approval Package. Acknowledgement: We wish to thank all of the patients, Investigators and study personnel participating in this trial. Disclosure of Interest: J. Merrill Consultant for: Anthera Pharmaceuticals Inc, V. Strand Consultant for: Anthera, C. Hislop Shareholder of: Anthera, Employee of: Anthera, M. Gangal Shareholder of: Anthera, Employee of: Anthera, R. Martin Shareholder of: Anthera, Employee of: Anthera, K. Kalunian Consultant for: Anthera